Composition and other Ecological Characteristics of Mixed-species Bird Flocks of Temperate Forests in Himachal Pradesh, India - Chauhan, Anita; Jolli, Virat (Indian Forester, 2022)
The composition of a mixed-species bird flock in the mid-altitude Himalayan Moist Temperate forest of Shimla city, Shimla district, Himachal Pradesh, India was studied including other ecological characteristics such as the movement pattern, periodicity, feeding behaviour, location and home range, and seasonal characteristics and migrants. The data was compared with the only previous study on MSB flocks from western Himalaya from 1977. The present study revealed the composition of the MSB flock as having mainly resident birds as 16 core species (including six nuclear species), and as many as 12 associate species. At least 30 of the 44 migrant species recorded were found to associate with MSB flocks; and migrant species were recorded in 64.3% of flock observations. The ecological characteristics described in this study have wide-ranging implications for bird survey techniques, habitat management and conservation planning.